OPEN TRANSPERITONEAL PYELOPLASTY IN CHILDREN: A SINGLE CENTRE EXPERIENCE - Dr. Udayabhanu Dhal; Dr. Sribatsa Nayak; Dr. Madam Mohan Majhi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Open pyeloplasty for PUJ obstruction is routinely performed through retro peritoneal route. There are little data to show  the significance of  trans peritoneal approach for open pyeloplasty.Objectives: To evaluate the results and complications of open Anderson hynes pyeloplasty done via trans peritoneal approach.Methods: We retrospectively reviewed the medical records of  38 children operated via transperitoneal open pyeloplasty (TOP) between 2019 to 2023. Patients demographic characteristics, operative time,estimated blood loss(EBL), post operative complications, success rate assessed by change in degree of hydronephrosis based on measurement of antero-posterior (AP)diameter of renal pelvis and increase in parenchymal thicknes were recorded.Results: Mean operative time was 90 minutes(80-110 min), mean EBL (Estimated blood loss) was 15ml(10-30ml). The mean hospital stay was 5days(4-7days) days. Post operative ultrasound examination showed a diminished grade of hydronephrosis and improvement in renal function in diuretic scintigraphy. Over all success rate was 93%.Conclusion: Our result confirms that operation through transperitoneal route is within an acceptable range with a short learning curve. The advantage of a good exposure and operating  over pelvi ureteric junction in a normal anatomical position is really helpful for beginers and operating in small infants.